(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
The reactive intermediate generated by the addition of alkyl isocyanides to dialkyl acetylenedicarboxylate are trapped by 3-hydroxyisoquinoline to produce highly functionalized 4H-chromenes in 83-92% yields.